Effects of dexmedetomidine in conjunction with remote ischemic preconditioning on renal ischemia–reperfusion injury in rats - Emine Bagcik; Sevda Ozkardesler; Nilay Boztas; Bekir Ugur Ergur; Mert Akan; Mehmet Guneli; Sule Ozbilgin (Brazilian Journal of Anesthesiology, 2014)
Background and objectives: The aim of this study was to evaluate the effects of remote ischemic preconditioning by brief ischemia of unilateral hind limb when combined with dexmedetomidine on renal ischemia–reperfusion injury by histopathology and active caspase-3 immunoreactivity in rats. Methods: 28 Wistar albino male rats were divided into 4 groups. Group I (Sham, n = 7): Laparotomy and renal pedicle dissection were performed at 65th minute of anesthesia and the rats were observed under anesthesia for 130 min. Group II (ischemia–reperfusion, n = 7): At 65th minute of anesthesia bilateral renal pedicles were clamped. After 60 min ischemia 24 h of reperfusion was performed. Group III (ischemia–reperfusion + dexmedetomidine, n = 7): At the fifth minute of reperfusion (100 μg/kg intra-peritoneal) dexmedetomidine was administered with ischemia–reperfusion group. Reperfusion lasted 24 h. Group IV (ischemia–reperfusion + remote ischemic preconditioning + dexmedetomidine, n = 7): After laparotomy, three cycles of ischemic preconditioning (10 min ischemia and 10 min reperfusion) were applied to the left hind limb and after 5 min with group III. Results: Histopathological injury scores and active caspase-3 immunoreactivity were significantly lower in the Sham group compared to the other groups. Histopathological injury scores in groups III and IV were significantly lower than group II (p = 0.03 and p = 0.05). Active caspase-3 immunoreactivity was significantly lower in the group IV than group II (p = 0.01) and there was no significant difference between group II and group III (p = 0.06). Conclusions: Pharmacologic conditioning with dexmedetomidine and remote ischemic preconditioning when combined with dexmedetomidine significantly decreases renal ischemia–reperfusion injury histomorphologically. Combined use of two methods prevents apoptosis via active caspase-3. Resumo: Justificativa e objetivos: Avaliar os efeitos do pré-condicionamento isquêmico remoto, mediante breve isquemia de membro posterior unilateral, em combinação com dexmedetomidina em lesão de isquemia-reperfusão renal por meio de histopatologia e imunorreatividade da caspase-3 ativa em ratos. Métodos: Foram divididos em quatro grupos 28 ratos machos albinos Wistar. Grupo I (Sham [cirurgia controle], n = 7): laparotomia e dissecção do pedículo renal foram feitas em 65 minutos de anestesia e os ratos foram observados sob anestesia por 130 minutos. Grupo II (isquemia-reperfusão, n = 7): no 65° minuto de anestesia, os pedículos renais bilaterais foram pinçados; após 60 minutos de isquemia, foi feita reperfusão de 24 horas. Grupo III (isquemia-reperfusão + dexmedetomidina, n = 7): no quinto minuto de reperfusão, dexmedetomidina (100 mg/kg intraperitoneal) foi administrada ao grupo com isquemia-reperfusão. A reperfusão durou 24 horas. Grupo IV (isquemia-reperfusão + pré-condicionamento isquêmico remoto + dexmedetomidina, n = 7): após a laparotomia, três ciclos de pré-condicionamento isquêmico (10 minutos de isquemia e 10 minutos de reperfusão) foram aplicados no membro posterior esquerdo e depois de cinco minutos ao grupo III. Resultados: Os escores de lesão histopatológica e imunorreatividade da caspase-3 ativa foram significativamente menores no grupo Sham em comparação com os outros. Os escores de lesão histopatológica dos grupos III e IV foram significativamente menores do que os do II (p = 0,03 e p = 0,05). A imunorreatividade da caspase-3 foi significativamente menor no grupo IV do que no II (p = 0,01) e não houve diferença significante entre os grupos II e III (p = 0,06). Conclusões: O condicionamento farmacológico com dexmedetomidina e o pré-condicionamento isquêmico remoto em combinação com dexmedetomidina diminuem de modo significante a lesão de isquemia-reperfusão renal histomorfologicamente. O uso combinado dos dois métodos previne a apoptose via caspase-3 ativa. Keywords: Kidney, Ischemia–reperfusion injury, Dexmedetomidine, Caspase-3, Ischemic preconditioning, Apoptosis, Palavras-chave: Rim, Lesão de isquemia-reperfusão, Dexmedetomidine, Caspase-3, Pré-condicionamento isquêmico, Apoptose